Differentiated approach to treatment of severe acute pancreatitis based on organ failure pattern - Levytskyi, H. O.; Sheiko, V. D. (General Surgery, 2025)
Severe acute pancreatitis (SAP) complicated by organ failure (OF) is associated with mortality rates of 15 – 40%. While the step‑up approach has proven superior to primary necrosectomy, its universal application fails to account for the heterogeneity of clinical trajectories. Early stratification of patients based on OF patterns may facilitate the development of personalised treatment protocols. Objective – to evaluate the effectiveness of a differentiated treatment approach to severe acute pancreatitis based on organ failure patterns in comparison to standard disease management. Materials and methods. A quasi‑experimental study with historical control was conducted in 77 patients with SAP or high risk of its development. The comparison group (n=41, 2014 – 2019) received standard treatment with retrospectively confirmed OF development. The main group (n=36, 2022 – 2024) underwent prospective stratification using a prognostic model within 24 hours of admission, identifying three OF patterns: early respiratory‑renal, late respiratory, and early multisystem. Pattern‑specific protocols were applied: aggressive early drainage for the early respiratory‑renal pattern, a maximal conservative approach for the late respiratory pattern, and intensive monitoring with readiness for emergency interventions for the early multisystem pattern. The primary endpoint was hospital length of stay (LOS). Secondary endpoints included OF development, intensive care unit (ICU) utilisation, surgical interventions, and mortality. Results. Median hospital LOS decreased from 35 [23 – 65] to 27 [15 – 33.25] days (p=0.015), representing a 22.9% reduction. OF development was prevented in 33.3% of high‑risk patients (the number needed to treat is 3). The incidence of persistent OF decreased from 90.2% to 50.0% (odds ratio (OR)=0.11, 95% confidence interval (CI): 0.03 – 0.37, p<0.0001), and multiorgan failure from 31.7% to 5.6% (p=0.004). The treatment effect was pattern‑dependent (interaction p<0.0001): the late respiratory pattern showed a 44.4% LOS reduction (61.1±27.2 to 34.0±23.6 days, p=0.005), the early multisystem pattern demonstrated a 47.2% reduction (50.2±32.8 to 26.5±19.3 days, p=0.042), while the early respiratory‑renal pattern showed a non‑significant increase (+31.3%, p=0.870). The proportion of staged open operations decreased from 58.5% to 22.2% (p=0.001) without affecting emergency surgery rates. Mortality decreased from 12.2% to 8.3% (p=0.579). Conclusions. Pattern‑oriented treatment of SAP significantly reduces hospitalisation duration and prevents OF development in one‑third of high‑risk patients. Treatment efficacy is heterogeneous across patterns, with the greatest benefit observed in late respiratory and early multisystem variants. This approach transforms the surgical paradigm from reactive to proactive, optimising intervention timing based on predicted clinical trajectory. Further multicentre validation is warranted to confirm these findings.